The Importance of Creativity in Human Resource Management to Achieve Effective Administration - Rustiawan, Indra; Amory, Jeffriansyah Dwi Sahputra; Kristanti, Desi (ADMAN: Journal of Contemporary Administration and Management, 2023)
In an increasingly competitive and rapidly changing business era, human resource management has become a key element in corporate success. Effective administration requires human resources who are high-performing, innovative, and able to adapt to dynamic changes in the business environment. Creativity, as the ability to generate new ideas and innovative solutions, is an important factor in achieving this goal. This research aims to examine the importance of creativity in human resource management to achieve effective administration. It is an exploration of the literature that adopts a qualitative method, which means that it evaluates and interprets information and texts that come from a variety of different sources. The results of the study show that in human resource management, creativity is a key element that plays a role in achieving effective administration. Creativity helps organisations to adapt quickly, increase employee motivation, and create an innovative environment. Through the development of a culture that supports creativity and strategies that encourage the contribution of innovative ideas from employees, organisations can harness the full potential of their human resources.